2021
DOI: 10.1371/journal.ppat.1009800
|View full text |Cite|
|
Sign up to set email alerts
|

SARS-CoV-2 suppresses IFNβ production mediated by NSP1, 5, 6, 15, ORF6 and ORF7b but does not suppress the effects of added interferon

Abstract: Type I Interferons (IFN-Is) are a family of cytokines which play a major role in inhibiting viral infection. Resultantly, many viruses have evolved mechanisms in which to evade the IFN-I response. Here we tested the impact of expression of 27 different SARS-CoV-2 genes in relation to their effect on IFN production and activity using three independent experimental methods. We identified six gene products; NSP6, ORF6, ORF7b, NSP1, NSP5 and NSP15, which strongly (>10-fold) blocked MAVS-induced (but not TRIF-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
121
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(125 citation statements)
references
References 80 publications
4
121
0
Order By: Relevance
“…SARS-CoV nsp-1 (nanostructural protein 1) suppresses the immune response along with the generation of IFNs (IFN-I). nsp demonstrates an elevated expression of IFN-I [ 83 ]. Activation of IFN-I also minimize the expression of viral proteins such as nsp1, nsp7, and nsp15, as well as ORFs such as ORF3B, ORF6, and ORF9b [ 84 ].…”
Section: Infection Mechanism Of Sars-cov-2mentioning
confidence: 99%
“…SARS-CoV nsp-1 (nanostructural protein 1) suppresses the immune response along with the generation of IFNs (IFN-I). nsp demonstrates an elevated expression of IFN-I [ 83 ]. Activation of IFN-I also minimize the expression of viral proteins such as nsp1, nsp7, and nsp15, as well as ORFs such as ORF3B, ORF6, and ORF9b [ 84 ].…”
Section: Infection Mechanism Of Sars-cov-2mentioning
confidence: 99%
“… 196 Moreover, Nsp6 can strongly blocked MAVS (mitochondrial antiviral signaling protein)-induced interferon β production and binds TANK binding kinase1 (TBK1) to suppress interferon regulatory factor 3 (IRF3). 197 , 198 Nsp6 also interacts with the sigma-1 receptor, which is considered an effective candidate host protein for host-based repurposing approaches to treat COVID-19 patients. 199 So far, there is no available structural information for Nsp6.…”
Section: Nonstructural Proteins Of Sras-cov-2mentioning
confidence: 99%
“…Among these, nucleocapside (N) protein impedes type I IFN signaling by preventing the nuclear translocation of phosphorylated STAT1 and STAT2 [21] . A recent study identified six SARS-CoV-2 genes that block mitochondrial antiviral signaling protein (MAVS)-induced production of IFN-β, but not of IFN-α or IFN-γ [22] . Studies comparing peripheral immune responses in mild and severe COVID-19 patients report diminished type I IFN levels in severe cases versus mild cases, and restricted IFN-stimulated gene (ISG) expression among circulating immune cells [23] , [24] , [25] .…”
Section: The Early Cytokine and Cellular Response To Sars-cov-2 Infectionmentioning
confidence: 99%